Analisa Motor Gearbox N20 Untuk Prototipe Katrol Pengering Pakaian Otomatis Berbasis Mikrokontroler Untuk Daerah Pegunungan Nongkojajar Pasuruan - Muhammad Badaruz Zaman; Subekhan Makhrus (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The sun is the primary source of energy for human life, both in the form of light and heat. In mountainous areas such as Nongkojajar, Pasuruan, low sunlight intensity and high rainfall often hamper the clothes-drying process. This condition creates a need for automated solutions that can assist people in their daily activities. This research aims to design and test the effectiveness of a microcontroller-based automatic clothes dryer pulley prototype, which can operate independently based on sunlight intensity. This device uses a light sensor to detect cloudy weather and automatically pulls the clothesline indoors. This research is expected to provide practical solutions for communities in mountainous areas, while also increasing knowledge regarding the application of microcontroller-based automated systems.